2023
DOI: 10.1002/anie.202314996
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Selective Luminescent Sensing by Langmuir–Schaeffer Films Based on Controlled Assembly of Perylene Bisimide Modified with A Cyclometalated AuIII Complex

Jing Zhang,
Zhiwei Shi,
Ke Liu
et al.

Abstract: Condensed films of functional luminophores dominated by the magnitude and dimensionality of the intermolecular interactions play important roles in sensing performance. However, controlling the molecular assembly and regulating photophysical properties remain challenging. In this study, a new luminophore, ortho‐PBI‐Au, was synthesized by anchoring a cyclometalated alkynyl‐gold(III) unit at the ortho‐position of perylene bisimide. An unprecedented T‐type packing model driven by weak Au‐π interaction and Au‐H bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Figure 7c showed the flowchart of the sensor identification process for suspicious personnel, aiming to create a simplified workflow to meet new requirements for body fluid testing in drugfacilitated crime investigations. 30,48 Baseline correction was used to eliminate the background interference signals when the indicator flowed into the sensing platform. A constant I 0 value was obtained as the processed signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure 7c showed the flowchart of the sensor identification process for suspicious personnel, aiming to create a simplified workflow to meet new requirements for body fluid testing in drugfacilitated crime investigations. 30,48 Baseline correction was used to eliminate the background interference signals when the indicator flowed into the sensing platform. A constant I 0 value was obtained as the processed signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…27). 82 The micro-morphology of the obtained LS films was thoroughly characterized using microscopy techniques. The sensing experiments indicated that films fabricated on different surface pressures displayed varying responses to phenylethylamine vapor, primarily due to their differences in film thickness and porosity.…”
Section: Fabrication and Engineering Of Active-layer Structuresmentioning
confidence: 99%